2022
DOI: 10.1021/acsomega.2c01334
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Optical, and Magnetic Properties of Erbium-Substituted Yttrium Iron Garnets

Abstract: We synthesized a series of slightly erbium-substituted yttrium iron garnets (Er:YIG), Y 3– x Er x Fe 5 O 12 at different Er concentrations ( x = 0, 0.01, 0.05, 0.10, and 0.20) using a solid-state reaction and investigated their structural, magnetic, and optical properties as a function of Er concentration. The volume of the unit cell slightly increased with Er concentration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
(73 reference statements)
1
3
0
Order By: Relevance
“…The strongest peak in the spectrum of Co 9 Er 1 O x exists at a k value of ∼6.12 Å –1 , and an R value of ∼1.40 Å indicates the existence of Co-O coordination similar to that of Co 2 O 3 , while the disappearance of peaks at higher k and R values for the Co-Co configuration confirms the ultrasmall size of Co species. Figure d,e shows the XANES and EXAFS curves of Co 9 Er 1 O x at the Er L 3 -edge, in which the curve shapes are all very similar to that of Er 2 O 3 reported in the literature, suggesting the presence of the Er 2 O 3 composition in Co 9 Er 1 O x . Based on the above results, it can be concluded that the Co 9 Er 1 O x catalyst is mainly CoO x (with Co 3+ ) tiny particles dispersed on the Er 2 O 3 substrate, with a strong particle-substrate interaction to facilitate the reaction.…”
supporting
confidence: 76%
“…The strongest peak in the spectrum of Co 9 Er 1 O x exists at a k value of ∼6.12 Å –1 , and an R value of ∼1.40 Å indicates the existence of Co-O coordination similar to that of Co 2 O 3 , while the disappearance of peaks at higher k and R values for the Co-Co configuration confirms the ultrasmall size of Co species. Figure d,e shows the XANES and EXAFS curves of Co 9 Er 1 O x at the Er L 3 -edge, in which the curve shapes are all very similar to that of Er 2 O 3 reported in the literature, suggesting the presence of the Er 2 O 3 composition in Co 9 Er 1 O x . Based on the above results, it can be concluded that the Co 9 Er 1 O x catalyst is mainly CoO x (with Co 3+ ) tiny particles dispersed on the Er 2 O 3 substrate, with a strong particle-substrate interaction to facilitate the reaction.…”
supporting
confidence: 76%
“…When YIG is doped with erbium (Er), the magnetic moment is not influenced much over a wide temperature range except below 30K where the unpaired 4f electrons are coupled antiparallelly with the 3d electrons of iron cations [34]. Thus Er:YIG exhibits antiferromagnet-like behaviour at this lower temperature whereas above this and at room temperature it exhibits ferromagnetic behaviour.…”
Section: Magnetic Properties Of Yigmentioning
confidence: 99%
“…Among them, the dodecahedral c-site can accommodate rare earth ions with a large radius, while the tetrahedral a-site and octahedral d-site are typically used for doping ions with a smaller radius. 10,11 So far, there have been many reports on the modification of yttrium iron garnets by ions doping, especially Ce 3+ and Bi 3+ ions have been confirmed to have a significant effect on the improvement of magnetooptical properties. 12−15 16 Aung et al reported Bi 3+ ion-doped Bi x Y 3−x Fe 5 O 12 (x = 0−1.1) ceramics, which possess a FRA of −970°/cm at 1550 nm.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that the structure possesses three sites: a-site, c-site, and d-site. Among them, the dodecahedral c-site can accommodate rare earth ions with a large radius, while the tetrahedral a-site and octahedral d-site are typically used for doping ions with a smaller radius. , So far, there have been many reports on the modification of yttrium iron garnets by ions doping, especially Ce 3+ and Bi 3+ ions have been confirmed to have a significant effect on the improvement of magneto-optical properties. Ikesue et al reported that Ce 0.24 Y 2.76 Fe 5 O 12 ceramic was prepared by hot isostatic press and atmosphere sintering technology, and the FRA of Ce 0.24 Y 2.76 Fe 5 O 12 ceramic at 1550 nm band can reach 990°/cm . Aung et al reported Bi 3+ ion-doped Bi x Y 3– x Fe 5 O 12 ( x = 0–1.1) ceramics, which possess a FRA of −970°/cm at 1550 nm .…”
Section: Introductionmentioning
confidence: 99%